2013
DOI: 10.1128/aem.00515-13
|View full text |Cite
|
Sign up to set email alerts
|

ProP Is Required for the Survival of Desiccated Salmonella enterica Serovar Typhimurium Cells on a Stainless Steel Surface

Abstract: dConsumers trust commercial food production to be safe, and it is important to strive to improve food safety at every level. Several outbreaks of food-borne disease have been caused by Salmonella strains associated with dried food. Currently we do not know the mechanisms used by Salmonella enterica serovar Typhimurium to survive in desiccated environments. The aim of this study was to discover the responses of S. Typhimurium ST4/74 at the transcriptional level to desiccation on a stainless steel surface and to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
82
1
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
2
2
2

Relationship

0
6

Authors

Journals

citations
Cited by 76 publications
(88 citation statements)
references
References 61 publications
(90 reference statements)
4
82
1
1
Order By: Relevance
“…Our finding is consistent with data from some previous studies (12,14,15). These observations may indicate that while the formation of filaments may be critical for long-term persistence in low-a w environments, this may not be the case when bacteria are desiccated under certain conditions, such as in aged broiler litter.…”
Section: Discussionsupporting
confidence: 83%
See 4 more Smart Citations
“…Our finding is consistent with data from some previous studies (12,14,15). These observations may indicate that while the formation of filaments may be critical for long-term persistence in low-a w environments, this may not be the case when bacteria are desiccated under certain conditions, such as in aged broiler litter.…”
Section: Discussionsupporting
confidence: 83%
“…Conflicting results, however, were obtained in the present study; no induction of the fadA gene was detected in S. Typhimurium under desiccation conditions in aged broiler litter (P Ͼ 0.05). Similarly, some authors also observed no expression of the fadA gene in Salmonella in response to various desiccation conditions (11,12,14). This discrepancy could possibly be accounted for by the different water activities accompanying different methods used to develop a desiccation environment.…”
Section: Discussionmentioning
confidence: 92%
See 3 more Smart Citations